2015
DOI: 10.1210/jc.2015-2872
|View full text |Cite
|
Sign up to set email alerts
|

Altered Circulating miRNA Expression Profile in Pregestational and Gestational Obesity

Abstract: This study provides the first identification of altered circulating miRNAs in maternal obesity and suggests a possible role of such miRNAS as markers for pre- and postnatal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1
15

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 40 publications
1
51
1
15
Order By: Relevance
“…The small sample size in the epigenome-wide miRNA expression profiling may have increased imprecision of statistical estimates. Our study, however, is similar in size to the lone previous analysis of miRNA levels in maternal plasma in relation to obesity 21 . The large number of tests we conducted in the analyses of the epigenome-wide profiling data may increase the likelihood of false positives.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The small sample size in the epigenome-wide miRNA expression profiling may have increased imprecision of statistical estimates. Our study, however, is similar in size to the lone previous analysis of miRNA levels in maternal plasma in relation to obesity 21 . The large number of tests we conducted in the analyses of the epigenome-wide profiling data may increase the likelihood of false positives.…”
Section: Discussionsupporting
confidence: 82%
“…These included miR-130b, (targeting PPARG), let-7 (targeting HMGA2, E2F6, and CDC34), -103 (targeting ARNT, FZD1, RUNX1T1, ETO, MTG8, PDK1 and WNT3A), -221/222 (targeting CDKN1B and p27), -423-5p (targeting CD1C), -26 (targeting EZH2 and SMAD1), -128-2 (targeting TXNIP), -146b (targeting NFKB), -29 (targeting HDAC4), -425 (targeting PTEN) and -376 (targeting ATG4C and BECN1). 1221, 2938 It is important to note that the direction of associations (upregulation or downregulation) for some of these miRNAs was not similar in several of the studies, including our own. This may be due to differences in samples used for the expression measurements, and needs further investigation.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Analysis of these vesicles showed that miR-30a-5p (miR-30a) was one of the most enriched miRs. miR-30a is particularly interesting as increased expression is associated with ischemia and vascular comorbidities such as obesity, diabetes, stroke, and subarachnoid hemorrhage (Carreras-Badosa et al, 2015;Long et al, 2013;Muller et al, 2015;Nielsen et al, 2012). Finally, miR-30a is highly expressed in proliferating endothelial cells in vitro (Anand et al, 2010), is enriched in microglia (Butovsky et al, 2014), and has recently been shown to be one of the 10 most abundant miRNAs in the human retina (Karali et al, 2016).…”
mentioning
confidence: 99%